Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 17 - Section 17.4 - Series Solutions - 17.4 Exercise - Page 1180: 1


$y=C_{0} e^{x}$

Work Step by Step

Given: $y' - y = 0$ Since, $y=\Sigma^\infty_{n=1}C_{n} x^{n}$ Here, we have $y'=\Sigma^\infty_{n=0}C_{n+1}(n+1) x^{n}$ Then, the given equation $y' - y = 0$ becomes: $\Sigma^\infty_{n=0}C_{n+1} (n+1)x^{n}$ - $\Sigma^\infty_{n=1}C_{n}x^{n}=0$ or, $\Sigma^\infty_{n=0}[C_{n+1}(n+1) - C_{n}]=0$ For n=0 , we have $C_{1} = C_{0}$; For n=1 , we have $C_{2} = \dfrac{C_{0}}{2}=0$; For n=2 , we have $C_{3} = (\dfrac{1}{3}) (\dfrac{1}{2}) \times C_{0}=0$ Thus, we get $C_{n} = \dfrac{C_0}{n!}$ We know that $ \Sigma^\infty_{n=0} \dfrac{x^n}{n!}=e^{x} $ Hence, $y=C_{0} e^{x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.